2012
DOI: 10.5539/ies.v5n3p15
|View full text |Cite
|
Sign up to set email alerts
|

The Moral Reasoning of Adolescent Boys and Girls in the Light of Gilligan’s Theory

Abstract: The study was conducted to assess the moral reasoning of adolescent boys and girls in the light of Gilligan theory. The main objectives of the study were to investigate the moral reasoning of adolescent boys and girls with reference to responsibility orientation versus justice orientation and to compare the frequency of adolescent boys and girls with right orientation and responsibility orientation. The population of study consisted of all adolescent boys and girls studying in SSC and F.A/FSc of Fazaia Inter C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…Many studies using the work of Carol Gilligan and others have found gender differences in moral orientation. [79][80][81] Perhaps the differences could be explained this way. This study partially supports Gilligan's theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies using the work of Carol Gilligan and others have found gender differences in moral orientation. [79][80][81] Perhaps the differences could be explained this way. This study partially supports Gilligan's theory.…”
Section: Discussionmentioning
confidence: 99%
“…This study partially supports Gilligan's theory. 79,80 It has been observed that cultural norms play an important role to make the men more assertive than women. Socialization patterns of both are different.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, inadequate moral upbringing, proper monitoring and adequate supervision on the parents' part may lead adolescents to be involved in immoral behavior (Ajidahun, 2014). Kalsoom et al (2012) reported that the most important factor which influences moral judgment and justice orientation is religion. A study with the Barna Group (2018) revealed that the Generation Z is the least Christian and most racially, religiously, and sexually diverse generation.…”
Section: Discussionmentioning
confidence: 99%
“…This was also revealed by Kalsoom (2012) that Kohlberg used the results of the Swiss psychologist, Jean Piaget's research on the development of human knowledge to find out the stages of development of moral consciousness. However, the moral development offered by Kohlberg with justice oriented was criticized by Gilligan (1985) that moral is not only based on justice but rather an ethics of caring and dominated not by male or female figures.…”
Section: Introductionmentioning
confidence: 91%